Taxonomic and phylogenetic diversity of herbaceous-shrub species in veredas (brazilian savanna palm swamps) and factors that determine their composition and distribution - Bijos, Natália Rodrigues (2024)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Biológicas, Programa de Pós-Graduação em Ecologia, 2024.